Dynamic mechanical and shape memory properties of polybenzoxazines based on aminopropyl‐terminated siloxanes. Issue 42 (13th July 2016) - Su, Xuehui; Song, Shuning; Zhang, Chunhui; Huang, Jinbai; Liu, Yanfang; Run, Mingtao; Wu, Yonggang
ABSTRACT: Four siloxane‐containing benzoxazine monomers and telechelic benzoxazine oligomers were synthesized from 1, 3‐bis(3‐aminopropyl)‐1, 1, 3, 3‐tetramethyldisiloxane, α, ω‐bis(3‐aminopropyl)polydimethylsiloxane, phenol, o ‐allylphenol, and formaldehyde. The length of the siloxane segment affects the polymerization reaction of the benzoxazine monomers and telechelic benzoxazine oligomers. The dynamic mechanical properties of the corresponding polybenzoxazines depend primarily on the structure of phenol and the length of the siloxane segment. The polybenzoxazines exhibit one‐way dual‐shape memory behavior in response to changes in temperature. The thermally induced shape memory effects of the polybenzoxazines were characterized by bending and tensile stress–strain tests with a temperature program based on their glass transition temperatures. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 44121. Abstract :